Pete Rose's winning baseball - Rose, Pete, 1941-; Hertzel, Bob, 1941- (Chicago : H. Regnery Co., 1976)
Examines different baseball skills such as hitting, running, playing the various field positions and pitching.
Includes index.
Keywords: Baseball; Baseball